DIURNAL BIRD COMMUNITY STRUCTURE AROUND THE WAILOI RIVER, OF HILA KAITETU (LEIHITU DISTRICT) MALUKU - Saman, Risna; Moniharapon, Mechiavel; Eddy, La (RUMPHIUS, 2019)
Birds are very dynamic and are found almost everywhere. The purpose of this study was to determine the community structure of diurnal birds around the Wailoi Negeri Hila Kaitetu River, Leihitu District, Central Maluku Regency. The type of this research was quantitative descriptive in nature. The method used is the station line method combined with the count point. The results showed that in the Wailoi River, Negeri Hila Kaitetu, with 2 stations and 11 counting points, several species of diurnal birds were found, namely the type of Trinil beach (Actitis hypoleucos), Tiger Kestrel (Falco severus), Gray Flycatcher (Myagra galeata), Red- cheeked Lorike. (Geoffroyus geoffroyi), Terkukur common (Streptopelia chinensis), Wiwik Jungle (Cacomantis variolosus), Hornbill Irian (Rhyticeros plicatus), Nuri Maluku (Eos borneo), King Prawn Erasia (Alcedo atthis), Pacific Baza (Aviceda subcristata), Small perling (Aplonis minor), Lazuli Checkfish (Halcyon lazuli), Dotted Flycatcher (Muscicapa griseisticta), Sriganti sunbird (Nectarinia jugularis), Asian Tuwur (Eudynamys cyanochepala), Black honey (Necterinia aspesia), Pergam tarut (Ducula concinna). The diversity index for the 2 stations was 1.74 and classified as moderate species diversity criteria. For the average dominance value of station I and station II, which is 0.24, it is included in the low dominance criteria. The evenness value of the two stations is 0.80 and is included in the criteria for a high level of evenness.